Perilaku Cuci Tangan Pakai Sabun Studi Kualitatif pada Ibu-Ibu di Kampung Nelayan Muara Angke Jakarta Utara; Studi Kualitatif - Intan Silviana Mustikawati (ARKESMAS [Arsip Kesehatan Masyarakat], 2017)
Washing Hand Behavior Using Soap Among Mothers’ of Underfive Children at Kampung Nelayan Muara Angke, Jakarta Utara. A Qualitative Study Introduction. The result of Joint Monitoring Program (JMP) showed the low prevalence of washing handusing soap at five critical important times.Objective. This study was aimed at gathering indepth information regarding the behavior as well as itssupporting factors and obstacles among mothers of underfive years old children living at a fishing villageMuara Angke, North Jakarta.Methods. The study employed qualitative approached and used purposive technique to got 5 informantsmothers of underfive years old childern, one informant from fishermen group and one puskesmas’ staff. Stepsin analyzing data consist of reducing data, presenting data, dan setting a conclusion. Results. Household mother informants aged 25-35 tahun, have highschool level of education. Family withmonthly income above Rp 3.000.000,00 installed pipewater fasilities. There is no public water fascilitiescould be used for washing hand, The Puskesmas had not conducted a PHBS campaign and public training.Most household informants comprehended what is and benefit of washing hand with soap, diseases could beprovoke by washing hand without soap; some mothers could state the critical important time to wash hand with soap; yet most of them could not state the steps and proper technique of healthy washing hand. Theattitude of informants toward washing hand was positive. Most informants report that they did not alwayswashing hand with soap at 5 critical times recommended and that their acts of washing hand were improper. Conclutions. With positive knowledge on and attitude toward washing hand with soap, the habit of proper washing of mothers could be improve through training and reduce the obstacle.